2012
DOI: 10.1074/jbc.m111.291898
|View full text |Cite
|
Sign up to set email alerts
|

Subunit Interactions and Cooperativity in the Microtubule-severing AAA ATPase Spastin

Abstract: Background: Spastin is a hexameric microtubule-severing AAA ATPase important for motoneuron integrity. Results: Enzymatic assays, microscopic severing assays, and inhibition experiments with ATP␥S and inactive mutant spastin reveal cooperativity of predominantly two subunits in spastin oligomers. Conclusion: Spastin hexamers show allosteric interactions among neighbor subunits, which disfavor random hydrolysis and concerted action models. Significance: This study sets a kinetic framework for spastin's severing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 45 publications
2
50
2
4
Order By: Relevance
“…N-terminal GFP fusions (GFP-Δ227 HsSpastin) were generated from the Δ227 human spastin GST expression vector used previously [8]. The protein was expressed in E. coli BL21(RIL), and purified by GSH-sepharose affinity, ion exchange, and gel filtration chromatography in buffers 1 and 2, as described (Eckert & al., Roll-Mecak & Vale, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…N-terminal GFP fusions (GFP-Δ227 HsSpastin) were generated from the Δ227 human spastin GST expression vector used previously [8]. The protein was expressed in E. coli BL21(RIL), and purified by GSH-sepharose affinity, ion exchange, and gel filtration chromatography in buffers 1 and 2, as described (Eckert & al., Roll-Mecak & Vale, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Evidently, one of the crucial steps of the severing process is the interaction with the microtubule. As other AAA ATPases, severing enzymes have been reported to be active in the form of homo-hexameric rings [5][8]. It has been hypothesized that the C-termini of α or β tubulin are threaded through the central pores of hexameric katanin or spastin rings [6], [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some subunits, such as Mcm4, Mcm5, and Mcm7, appear to have a greater contribution toward the overall MCM2-7 ATP hydrolysis rate than others, as mutations in their WB motifs result in stronger ATP hydrolysis defects (Bochman et al 2008;Bochman and Schwacha 2010;Bell and Botchan 2013). Many other ring-shaped hexameric motors show high cooperativity between active sites and sequential order of ATP hydrolysis (ATP hydrolysis in one subunit at the time following the order in the ring) (Abrahams et al 1994;Liao et al 2005;Adelman et al 2006;Thomsen and Berger 2008;Eckert et al 2012) but not all of them. For instance, studies on the hexameric protein unfoldase ClpX revealed that ATP hydrolysis in the hexamer is probabilistic.…”
Section: Mcm2-7 Atp Hydrolysis Activities Of the Occm Dh And Cmgmentioning
confidence: 99%
“…Spastin is a ring-shaped hexameric AAA ATPase that physically interacts with microtubules by ionic interactions [10] and severs them by enzymatic activity [11] at the expense of ATP hydrolysis energy [12]. …”
mentioning
confidence: 99%